A advocacia pública na resolução adequada das controvérsias envolvendo o poder público - Machado, Karine Pireddu Santana (2024)
This scientific work aims to analyze the role of municipal public law in applying appropriate means of resolving conflicts in demands involving the Public Treasury. The topic is not new. Much has already been written about the urgency of adopting what were previously called alternative means, replacing the sole action of the Judiciary. Despite the urgency of this measure, after approximately two decades of the creation of the National Policy for the adequate treatment of conflicts of interest within the scope of the Judiciary, the Public Administration remains refractory to the more incisive adoption of self-composition and mediation techniques, although it embodies one of the biggest litigators in Brazil. One of the most cited justifications for resistance to the adoption and improvement of these techniques is the necessary obedience to the principle of legality. Many decisions whose content could be more beneficial for citizens and the Public Administration itself are mistakenly taken due to lack of knowledge of the true extent of this principle, especially at the municipal level. Due to the fact that the administration of the Municipalities is so heterogeneous, composed of actors from the most varied areas and who, often, do not have the appropriate repertoire to achieve the ideal of efficiency, the role of the public lawyer is indispensable, both in the sphere judicial and extrajudicial. To obtain the results presented in the work, the deductive method was adopted, starting from general arguments to particular ones, using theoretical research, through doctrines and legislation relevant to the topic, in addition to research carried out by other professionals in the legal field. . The objective is to attempt to contribute to the expansion of the debate on the role of municipal public law in the adequate resolution of disputes related to public power, as well as to the dissemination of consensual resolution practices at the municipal level, contributing to a more transparent public administration it is efficient.